Computed Tomographic Evaluation of Bone Stock in Patients With Crowe Type III Developmental Dysplasia of the Hip: Implications for Guiding Acetabular Component Placement Using the High Hip Center Technique. - Liu, Bo; Gao, Yu-Hang; Ding, Lu; Li, Shu-Qiang; Liu, Jian-Guo; Qi, Xin (Journal of Arthroplasty, 2018)
Background: We evaluated acetabular cup coverage (CC) and rim contact (RC) to evaluate the bone stock above the acetabulum for guiding acetabular component placement using the high hip center technique in patients with Crowe type III developmental dysplasia of the hip.Methods: Using hip computed tomography and image processing software, pelvises were reconstructed digitally in 20 hips with Crowe type III developmental dysplasia of the hip. Mimicked cup was placed with anteversion angles of 0° (group I), 5° (group II), and 10° (group III) respectively. In each group, the cup was placed at the anatomical hip center at first, and then the cup was moved up to 40 mm vertically about the native rotation center with an increment of 2.5 mm at each step. CC and RC were calculated and documented with each movement.Results: CC was 65.87%, 67.77%, and 68.98% for group I, group II, and group III at the native rotation center, and increased progressively to 86.45%, 85.85%, and 84.71% at 25 mm above. RC was 49.17%, 50.25%, and 51.92% for group I, group II, and group III at the native rotation center, and increased progressively to 86.87%, 86.39%, and 84.94% at 22.5 mm above. CC and RC were positively correlated, despite the different anteversion angles (r = 0.687 at 0°, 0.683 at 5°, and 0.645 at 10°; P < .001).Conclusion: Computed tomography analysis and computer stimulation demonstrate that it is feasible to use high hip center technique in Crowe type III hips.